Ex vivo comparative study on three sinus lift tools for transcrestal detaching maxillary sinus mucosa. Issue 4 (4th July 2017) - Li, Yanfeng; Hu, Pin; Han, Yishi; Fan, Jiadong; Dong, Xinming; Ren, Huan; Yang, Chunhao; Shi, Tingting; Xia, Dong
ABSTRACT: The objective of this study was to comparatively evaluate 3 different sinus lift tools, namely umbrella-shaped sinus lift curette YSL-04, our recently designed probe-improved sinus lift curettes, and our newly invented elevator 014, using our previous developed goat ex vivo models for direct visualizing the effectiveness of detaching sinus mucosa in real time. Goat ex vivo models for direct visualizing the effectiveness of detaching sinus mucosa in real time were generated according to our previously developed protocol. The effectiveness for each tool was evaluated through the length of sinus mucosa detached in mesial and distal directions or buccal and palatal directions, and the space volume created by detaching maxillary sinus mucosa in mesial, distal, buccal and palatal directions. The results showed that all 3 sinus lift tools could transcrestally detach the maxillary sinus mucosa and create extra space under the elevated sinus floor on the goat ex vivo sinus models. Moreover, our newly invented elevator 014 had advantages over the other 2 in term of the capability to detach the sinus mucosa. Our newly invented elevator 014 might be a promising tool for detaching maxillary sinus mucosa in transcrestal maxillary sinus floor elevation.